Locally Simple Models Construction: Methodology and Practice - Kazakov, I. A.; Kustova, I. A.; Lazebnikova, E. N.; Mantsivoda, A. V. (Izvestiâ Irkutskogo gosudarstvennogo universiteta. Seriâ "Matematika" (Online), 2017)
One of the most notable trends associated with the Fourth industrial revolution is a significant strengthening of the role played by semantic methods. They are engaged in artificial intelligence means, knowledge mining in huge flows of big data, robotization, and in the internet of things. Smart contracts also can be mentioned here, although the ’intelligence’ of smart contracts still needs to be seriously elaborated. These trends should inevitably lead to an increased role of logical methods working with semantics, and significantly expand the scope of their application in practice. However, there are a number of problems that hinder this process. We are developing an approach, which makes the application of logical modeling efficient in some important areas. The approach is based on the concept of locally simple models and is primarily focused on solving tasks in the management of enterprises, organizations, governing bodies. The most important feature of locally simple models is their ability to replace software systems. Replacement of programming by modeling gives huge advantages, for instance, it dramatically reduces development and support costs. Modeling, unlike programming, preserves the explicit semantics of models allowing integration with artificial intelligence and robots. In addition, models are much more understandable to general people than programs. In this paper we propose the implementation of the concept of locally simple modeling on the basis of so-called document models, which has been developed by us earlier. It is shown that locally simple modeling is realized through document models with finite submodel coverages. In the second part of the paper an example of using document models for solving a management problem of real complexity is demonstrated.